Ecological analysis of demographic-, nutritional- and housing-related factors associated with anaemia among women of reproductive age group in Nigeria - Yusuf Olushola Kareem; Edward K. Ameyaw; Oluwasomidoyin O. Bello; Rukiyat A. Abdus-Salam; Olatunji O. Lawal; Gbolahan Obajimi; Yussuf Kofoworola Alade; Imran O. Morhason-Bello (BMC, 2022)
Abstract Introduction Anaemia remains a major public health concern, particularly, in sub-Saharan Africa (SSA), where it is one of the causes of maternal death. The most common cause of maternal anaemia is iron deficiency or malnutrition. This study examined the prevalence of and risk factors for anaemia among women that participated in the Nigerian Demographic Health Survey. Method We used data of 14,454 women that participated in the 2018 Nigeria Demographic and Health Survey (NDHS). We extracted information such as demographic, social and housing, dietary characteristics and haemoglobin concentration. The descriptive statistic results, prevalence and 95% confidence interval (CIs) of anaemia with the selected respondents background characteristics were presented. The Poisson regression model with robust variance was used to assess the risk of anaemia among women of reproductive age. All analyses were weighted and adjusted for the complex survey design. Statistical significance was interpreted at p value < 0.05. Results Maternal status, body mass index, education, residence, religion, ethnicity, region and type of cooking fuel were all important determinants of anaemia. The prevalence of anaemia was high among pregnant women (61.8%; 95% CI: 58.5-65.0), adolescents (60.4%; 95% CI: 58.1-62.6), underweight women (62.6%; 95% CI: 59.5-65.5), women who had no formal education (64.1%; 95% CI: 62.2-66.0) and those who belonged to the poorest wealth quintile (65.8%; 95% CI: 63.1-68.4). Similarly, anaemia was high among women residing in rural areas (61.5%; 95% CI: 60.0-63.0), Muslims (59.9%; 95% CI: 58.1-61.6) and women with six or more children (62.1%; 95% CI: 60.0-64.1). The risk of anaemia were 2% less likely among women who took minimum adequate diet compared to those who do not. Conclusion To date, this is the largest data on maternal anaemia in Nigeria. The study highlighted the high burden of maternal anaemia in the country and different risk factors (medical and social) that are associated with this medical condition among women of reproductive age. We recommend future longitudinal studies to test hypothesis in order to assess whether there is any causal relationship between identified risk factors and anaemia in this group of women.